STRATEGI MANAJERIAL KEPALA SEKOLAH DAN KOMPETENSI GURU DALAM PENGUATAN NILAI-NILAI ISLAM PADA PENDIDIKAN ANAK USIA DINI - Ngatmin Abbass; Apriliani, Elina Intan; Wardani, Anita; Mukhlisah, Iffah (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Abstract This study aims to analyze the principal’s strategy and teacher competence in strengthening Islamic values in early childhood education. The study is grounded in the importance of institutional leadership and teacher professionalism in fostering children’s religious habits, particularly amid the varied educational backgrounds of kindergarten and Raudhatul Athfal teachers. This research employed a quantitative approach with a descriptive survey design. Data were collected through questionnaires distributed to 17 respondents consisting of principals and teachers of TK/RA. The data were analyzed using descriptive statistics through frequencies, percentages, and score interpretation for each variable indicator. The findings reveal that the principal’s strategy falls within a very good category, particularly in planning Islamic value-based programs, providing direction, supervising instruction, guiding teachers, and creating a religious school environment. Teacher competence is also categorized as good to very good, especially in understanding Islamic education concepts, integrating Islamic values into learning activities, demonstrating exemplary behavior, and communicating effectively with children. The study concludes that strengthening Islamic values in early childhood is influenced by the synergy between school leadership and teacher competence in building a religious, supportive, and sustainable school culture.